â€œDINAMIKA FUNGSI PENGAWASAN DPRD TERHADAP PENGANGGARAN PUBLIKâ€ (Studi Kasus Pengawasan DPRD Terhadap Laporan Pertanggung jawaban Kepala Daerah Atas Pelaksanaan APBD Kabupaten Tabanan Tahun Anggaran 2013) - Ambarawati, Ni Luh Gede; Erviantono, Tedi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2015)
ABSTRACT Regional autonomy gives broad authority to the local government and legislature (DPRD). Tabanan district as one of the autonomous regions have the authority in managing the construction according to the characteristics based on local community needs. In the context of regional autonomy, parliament exercises oversight especially in the implementation of local revenue and expenditure budget (APBD). Oversight of the accountability report on the implementation of the budget is the final stage toi be held at the end of the fiscal year. However DPRD Tabanan on the realization of this oversight function is still not running optimally. See these problems, then the purpose of this study was to obtain a picture related to the actual implementation of the supervisory function of regency Tabanan against accountability report on implementation of the budget of region heads. This research uses qualitative descriptive method.The research findings indicate that the implementation of the supervisory function which is run by the local parliament Tabanan especially against the head of the region accountability report on implementation of the budget is still not optimal. This is caused by the first, the dominance of political factors that ultimately eliminates the essence of criticism and input from non-bearers of the party heads of regions. Second, the lack of adjustment and coordination of sectoral programs. This constraints that accurs because there is a clear agendas surveillance and reporting mechanisms monitoring results, not been determined by standard regulations implementating the oversight function of parliament and not optimal organization of all the resources of supervision. Keywords : Autonomy, Control of Parliament, Dynamics, Budget Accountability Report